Influence of hydraulic contact interface on drying process of masonry walls. Issue 9 (11th June 2020) - Delgado, J. M. P. Q.; Azevedo, A. C.; Guimarães, A. S.
Abstract: This work presents an extensive experimental characterization of two different ceramic brick blocks with hydraulic contact interface (cement mortar or lime mortar), at different heights, during the drying process. First, a laboratory characterization of the building material used (ceramic bricks and different mortars) was carried out to determine their hygrothermal, mechanical and thermal properties, namely, bulk porosity and density, water vapor permeability, capillary absorption, retention curve, moisture diffusivity as a function of moisture content and thermal conductivity. Finally, the moisture transfer in multi-layered systems was analyzed in detail taking into account the hydraulic contact between the building elements. The results showed an increase of the drying time constant for the materials with cement mortar interface compared to the lime mortars materials, and that as further away from the base the interface is located, higher is the drying time constant. The hydraulic interface (imperfect contact) could significantly retard the flow of moisture transport. i.e., the assumption of perfect hydraulic contact may result in significant error in predicting moisture transport in building materials.